The priest and the parson of Hartlepool: Protestant-Catholic conflict in a nineteenth-century industrial town. Issue 1 (31st March 2016) - Bush, Jonathan
Abstract : This article examines the role of Protestant-Catholic conflict in the English town of Hartlepool, a hitherto unknown centre of religious conflict during the nineteenth century. It will demonstrate how a combination of unique structural forces and the conduct of religious ministers created a culture which, in terms of ferocity and longevity, rivalled other sectarian centres in Britain. It also provides an important case study for examining the role of Catholics themselves in generating anti-Catholicism. It therefore has important implications for understanding the nature of religious conflict, how it develops, and how it is sustained over the longue durée .